Association Between Glycated Hemoglobin (HBA1C) Levels and The Incidence of Pulmonary Drug-Resistant Tuberculosis Among Patients With Type 2 Diabetes Mellitus - Kartini Harahap; Fajrinur Syarani; Bintang Yinke Magdalena Sinaga; Putri Chairani Eyanoer (Riviera Publishing, 2025)
Patients with type 2 diabetes mellitus (T2DM) are at increased risk of developing multidrug-resistant tuberculosis (MDR-TB). In Indonesia, data regarding the characteristics and risk factors for MDR-TB among diabetic populations remain limited. Managing MDR-TB in individuals with T2DM is complicated by potential drug interactions and challenges associated with poor glycemic control. This study aimed to assess the association between glycated hemoglobin (HbA1c) levels and the risk of developing MDR-TB among T2DM patients at Adam Malik General Hospital, Medan. A case-control analytical study was conducted using secondary data from medical records. A total of 120 participants were, including 60 MDR-TB cases and 60 drug-sensitive tuberculosis controls. Variables analyzed included age, sex, education, employment status, body mass index, smoking status, and HbA1c levels. Statistical analyses involved chi-square tests and multivariate logistic regression. Multivariate analysis identified smoking as the strongest risk factor for MDR-TB, followed by poor glycemic control, indicated by elevated HbA1c levels. Smoking substantially increases the risk of MDR-TB among patients with T2DM, with smokers being twelve times more likely to develop MDR-TB. These findings emphasize the need to integrate smoking cessation initiatives into MDR-TB prevention and management strategies targeting diabetic populations.